2015
DOI: 10.4314/bajopas.v8i1.26
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of biting and non-biting flies in relation to species in the Jos Museum Zoological Garden, north central Nigeria

Abstract: Several Dipteran flies are vectors of diseases in the Afro-tropical region. The study was carried out to determine the species abundance of biting and non biting flies prevalent at the Jos Museum Zoological Garden, north central Nigeria. The flies were trapped using Biconical traps during the raining season of August-September 2013. The flies were harvested three times a week at an interval of 48 hours. Stomoxys calcitrans is the most abundant species trapped. There were significantly more flies in the Lion, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…However, they did not report any of the Nematoceran flies. A similar study which was conducted by Njila et al (2015) at Jos Zoological garden reported the presence of house flies (Musca spp; non -biting fly) and stable fly (biting fly) among the flies collected around the wild life. However, the methods of collection differ, but his findings partially agreed with our results in areas of the presence of both house fly and stable fly around the livestock farm.…”
Section: Resultsmentioning
confidence: 64%
“…However, they did not report any of the Nematoceran flies. A similar study which was conducted by Njila et al (2015) at Jos Zoological garden reported the presence of house flies (Musca spp; non -biting fly) and stable fly (biting fly) among the flies collected around the wild life. However, the methods of collection differ, but his findings partially agreed with our results in areas of the presence of both house fly and stable fly around the livestock farm.…”
Section: Resultsmentioning
confidence: 64%
“…Physical injuries can occur due to bites from nonculicid biting flies and lead to secondary excoriations or ulcerative lesions. These injuries can lead to infections or scar tissue, negatively impacting animal well-being and reducing the attractiveness of animals on display (Njila et al 2015). In terms of behavior, animals may partake in more defensive behaviors at the expense of feeding or resting in response to high biting pressure (Ralley et al 1992, Toupin et al 1996.…”
Section: Discussionmentioning
confidence: 99%
“…The biological or epidemiological implications of larger populations of these species in the zoo is not known, but those more abundant species are known pests and/or vectors. Stomoxys calcitrans is a large, conspicuous species inflicting painful, stress-inducing bites that can cause physical damage to hosts (e.g., blisters and lesions) (Schwinghammer et al 1987, Catangui et al 1997, Njila et al 2015. The need for targeted control of stable flies in the zoo is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations